HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN POLA DIET PENDERITA DISPEPSIA DI PUSKESMAS TELUK DALAM KABUPATEN SIMEULUE - Baharuddin Baharuddin; Anasril Anasril (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Family support is an important factor in healing dyspepsia. Family support in this case is to encourage sufferers to comply with taking their medication, show sympathy and concern, and prevent the disease from recurring. In providing support for a member who suffers from dyspepsia, support from all family members is very important for the healing process and prevention of relapse. The purpose of this study was to determine the relationship between family support and adherence to the dietary pattern of dyspepsia patients at Teluk Dalam Public Health Center, Simeulue Regency. This type of research is descriptive analytic with the research design used is a cross sectional study, with a total sample of 31 patients with dyspepsia. Data analysis includes univariate analysis by looking for the frequency distribution, and bivariate analysis using chi-square test with a significance value (α= 0.05). The results showed that most respondents had family support in the good category as many as 18 people or about 58.1%, most of the respondents were obedient in following the diet pattern (51.6%). From the results of bivariate analysis, it is known that there is a relationship between family support and adherence to dietary patterns in patients with dyspepsia with a p value of 0.007 (p < 0.05). It is recommended to Health Officers at Teluk Dalam Health Center, Simeulue Regency to further improve health promotion about the importance of family support, especially in fulfilling a healthy diet for people with dyspepsia.